Determinants of Indonesia's Plantation Commodities Trade Flows with ASEAN: Insights from a Gravity Model Approach - Muhammad Ali Yafi; Amanda Sekar Adyanti (Universitas Muhammadiyah Malang, 2024)
The trade relationship between Indonesia and ASEAN countries in plantation products exhibits fluctuations in export and import activities. This study aims to identify the factors influencing Indonesia’s Plantation Commodities Trade Flows with ASEAN countries. The research utilizes secondary data from eight ASEAN countries-Indonesia, Cambodia, Malaysia, Singapore, Thailand, Vietnam, Myanmar, and the Philippines-over a 15-year period (2008–2022). A panel data regression analysis, based on the Gravity Model, was conducted to achieve the research objectives. The variables examined include Indonesia’s Plantation Commodities Trade Flows, Indonesia's GDP, partner countries' GDP, exchange rates, economic distance, population, and inflation. The analysis revealed that fluctuations in Indonesia’s Plantation Commodities Trade Flows are driven by variations in export and import values. The regression results identified Indonesia's GDP, partner countries' GDP, economic distance, and exchange rates as significant factors affecting trade flows, while population and inflation had no significant impact.